1999
DOI: 10.1016/s0022-2275(20)32108-8
|View full text |Cite
|
Sign up to set email alerts
|

VLDL-bound lipoprotein lipase facilitates the cholesteryl ester transfer protein-mediated transfer of cholesteryl esters from HDL to VLDL

Abstract: In recent years, it has been established that lipoprotein lipase (LPL) is partly associated with circulating lipoproteins. This report describes the effects of physiological amounts of very low density lipoprotein (VLDL)-bound LPL on the cholesteryl ester transfer protein (CETP)-mediated cholesteryl ester transfer (CET) from high density lipoprotein (HDL) to VLDL. Three patients with severe LPL deficiency exhibited a strong decrease in net mass CET that was more than 80% lower than that of common hypertriglyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…However, the main factor which is likely to be responsible for increased CETP activity, in type 1 diabetes, could be peripheral hyperinsulinemia secondary to the subcutaneous route of insulin administration. Indeed, peripheral hyperinsulinemia has been shown to be responsible for increased lipoprotein lipase activity in patients with type 1 diabetes (Nikkilä et al, 1977) and it has been reported that lipoprotein lipase, in presence of VLDL, enhances CETP activity (Sammett & Tall,1985;Pruneta et al, 1999). Moreover, it has been shown, in patients with type 1 diabetes, that the increase in both lipoprotein lipase and CETP activities was abolished when insulin was administrated intraperitoneously with implantable insulin pumps, mimicking the physiologic portal route or after pancreatic graft (Bagdade et al, 1994;.…”
Section: Lipid Transfer Proteinsmentioning
confidence: 99%
“…However, the main factor which is likely to be responsible for increased CETP activity, in type 1 diabetes, could be peripheral hyperinsulinemia secondary to the subcutaneous route of insulin administration. Indeed, peripheral hyperinsulinemia has been shown to be responsible for increased lipoprotein lipase activity in patients with type 1 diabetes (Nikkilä et al, 1977) and it has been reported that lipoprotein lipase, in presence of VLDL, enhances CETP activity (Sammett & Tall,1985;Pruneta et al, 1999). Moreover, it has been shown, in patients with type 1 diabetes, that the increase in both lipoprotein lipase and CETP activities was abolished when insulin was administrated intraperitoneously with implantable insulin pumps, mimicking the physiologic portal route or after pancreatic graft (Bagdade et al, 1994;.…”
Section: Lipid Transfer Proteinsmentioning
confidence: 99%